ENHANCING RETAKAFUL AND CAPITAL EFFICIENCY AND EFFECTIVENESS THROUGH FORMULATION OF OPTIMUM RETENTION - Wan Zamri Wan Ismail; Mohd Faiz Mohamed Yusof; Ismail Ahmad (International Journal of Accounting, Finance and Business, 2021)
The objective of this research is to highlight need for a takaful operator to enhance efficiency and effectiveness of its retakaful undertakings through the formulation of an optimum retention policy of the takaful risks underwritten before placement to retakaful. This is a qualitative study which discusses the theoretical and practical aspects of retakaful management with special reference to retention methodology through literature review and secondary data from published sources. This study highlights the practices of retakaful management in order to optimise risk retention by takaful operators. It outlines the theory and practice of risk retention undertaken in takaful business as a means to heighten the security, sustainability and growth of the Participants’ Risk Fund (PRF). This study contributes to the current dearth on literature and research on takaful and retakaful as a nascent industry, as compared to the more matured insurance and reinsurance industry. Hence, the conventional reinsurance management and practice is also referred as a benchmark. The study would provide better insight for the takaful industry in undertaking the retakaful management through a more efficient and effective retention methodology; supported by practical examples. Better understanding and management of retakaful in terms of retention policy by takaful operators based on a practitioner’s perspective in order to bolstering the technical and financial position of the PRF.